PROSPEK SEKTOR PERBANKAN INDONESIA: BEBERAPA AGENDA PENTING - Nopirin Nopirin (Faculty of Economics and Business, Universitas Gadjah Mada, 1998)
Globalization and the development of information technology has led to changes in the world financial system into an integrated market. The implication of this phenomenon is that the competition is getting fiercer. The restructuring of Indonesian banking is necessary in order to increase efficiency. The direction of banking activities toward electronic banking. The dominance of private banking is bigger and bigger. Merger is likely to happen. Credit allocation need to be scrutinized and directed more on productive activities not for consumtive purposes. Prudential credit policies should be taken in order to reduce bad loans. The banking sector should be sound. Another aspect for improving banking activities is monitoring by Bank Indonesia. Through improving stqf quality and using information technology monitoring and evaliation could be conducted efficiently. Last but not least is the human resource development through education and training. Well trained staff, able to utilized high technology together with high moral, ethic and have futuristic perspective is necessary condition for sound banking.